PAKET WISATA PEDESAAN KOTO SENTAJO KABUPATEN KUANTAN SINGINGI - Firda Widuri; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to make Rural Tour Packages based on tourism potential in Koto Sentajo Tourism Village of Kuantan Singingi Regency.This study used a qualitative method with descriptive approach, subjects of this study is Culture Tourism Office of Youth and Sports Kuantan Singingi, Koto Sentajo Tourism Village manager, owner of Rumah Godang and visitors. The data is collected by a study of documents, observation, interview, documentation.The result showed that Koto Sentajo village has tourism potential that displays cultural wisdom and life of rural communities. The cultural attraction in the village of Koto Sentajo is, Rumah Godang. Accommodation used by tourists is Rumah Godang as homestay. The tour package facility is handled directly by the tour guide. Accessibility to Koto Sentajo village is relatively good, The availability of transportation to enter the village of Koto Sentajo quite easy. Tour Package in the village of Koto Sentajo consists of rural tourism activities, agricultural education and outbound Activities carried out more likely to involve the surrounding environmentKeyword : Tour Packages, Rural, Koto sentajo